Organizações sem fins lucrativos e as parcerias com bandeiras de cartões de credito: responsabilidade social ou marketing? - Rocha, Michel Wiazowski (2012)
The nonprofits see growing in numbers and community service. Much has agreements with government, and operates in areas such as education, health, environment and social welfare. This study addresses partnerships between nonprofit organizations and banks. Check how these partnerships impact the services provided and how companies benefit from the sales of social products, and their use by marketing firms, and tax benefits arising from this relationship. It seeks to understand this relationship thatbenefits organizations with the use of credit cards by their members. The study begins by reviewing the literature on social responsibility and banks, then a search was made inbank branches and partner organizations, by conducting interviews with branch managers and directors of nonprofit organizations that maintains a partnership withbanks. The survey results reveal the importance of these partnerships for organizations, not only by the proceeds of the credit cards, but also the visibility that this partnership with banks brings to organizations. However, there is no transparency on the part of banks in relation to the amount of funds raised with the cards and the value of transfers to the organizations. Also missing for the employees of banks information about partner organizations and the sale of these products